Growth performance and carcass quality of broiler chickens as influenced by propriety source of feed (1999)
This study investigated the quality of selected popular poultry feeds available in Nigerian poultry feed market, using growth performance and carcass quality of broiler chickens as indices. Day old broiler chicks were fed with diets obtained from four different commercial feed manufacturers (coded FTE, GFE, PFE and SFE to protect the manufacturers) and control diet (formulated in conformity with recommended nutrient requirements for broiler chickens) over an eight week trial period. There were significant differences (P<0.05) in crude protein, fat and fibre contents of feeds. Crude protein contents of the commercial feeds were found to be below the recommendation level. In some of the feeds the crude fat and fibre contents were higher than the standard levels. The variation in feed quality resulted in reduced feed intake, lower average daily live weight gain, higher feed: gain ratio and lower nutrient retention (protein, fat, fibre) in broilers fed commercial diets when compared with birds on control diet. Live and carcass weight of birds placed on commercial diets FTE, PFE and SFE were significantly lower (P<0.05) than those placed on control diet. Since live and carcass weights of birds are the two major price indices in broiler chicken market, it was therefore concluded that most of the commercial feeds in Nigerian market were substandard.